A Confirmed Case of SARS-CoV-2 Pneumonia With Negative Routine Reverse Transcriptase–Polymerase Chain Reaction and Virus Variation in Guangzhou, China. (9th July 2020) - Li, Zhengtu; Li, Yinhu; Chen, Lingdan; Li, Shaoqiang; Yu, Le; Zhu, Airu; Yang, Feng; Jiang, Qian; Chen, Liyan; Zhao, Jincun; Lu, Wenju; Zhong, Nanshan; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia is a newly recognized disease, and its diagnosis is primarily confirmed by routine reverse transcriptase -polymerase chain reaction (RT-PCR) detection of SARS-CoV-2. Methods: However, we report a confirmed case of SARS-CoV-2 pneumonia with a negative routine RT-PCR. Results: This case was finally diagnosed by nanopore sequencing combined with antibody of SARS-CoV-2. Simultaneously, the ORF and NP gene variations of SARS-CoV-2 were found. Conclusions: This case highlighted that false-negative results could be present in routine RT-PCR diagnosis, especially with virus variation. Currently, nanopore pathogen sequencing and antibody detection have been found to be effective in clinical diagnosis. Abstract : A case was confirmed with SARS-CoV-2 pneumonia by nanopore pathogen sequencing and antibody detection. However, routine RT-PCR of SARS-CoV-2 was negative. Furthermore, it was shown to be negative by RT-PCR due to a viral mutation.